Political Machines at Work Voter Mobilization and Electoral Subversion in the Workplace. (28th March 2014) - Frye, Timothy; Reuter, Ora John; Szakonyi, David
<x content-type="archive" xml:space="preserve">Abstract</x> The authors explore how modern autocrats win elections by inducing employers to mobilize their employees to vote for the regime and thereby subvert the electoral process. using two original surveys of employers and workers conducted around the 2011 parliamentary elections in russia, they find that just under one-quarter of employers engaged in some form of political mobilization. they then develop a simple framework for identifying which firms engage in voter mobilization and which workers are targeted for mobilization. firms that are vulnerable to state pressure—financially dependent firms and those in sectors characterized by asset immobility—are among the most common sites of workplace-based electoral subversion. the authors also find that workers who are especially dependent on their employer are more likely to be targeted for mobilization. By identifying the conditions under which workplace mobilization occurs in authoritarian regimes, the authors contribute to the long-standing debate about the economic bases of democratization. in addition, they explore an understudied means of subverting elections in contemporary autocracies: the use of economic coercion to mobilize voters. Moreover, their research finds that clientelist exchange can thrive in industrial settings and in the absence of deeply embedded political parties.